2018
DOI: 10.2174/2211536607666180430153821
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Isolation and Amplification of microRNAs for Forensic Body Fluid Identification

Abstract: This research highlights the potential of miRNAs as novel markers for the identification of forensically relevant body fluids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Previous published studies reported promising results identifying differentially expressed miRNAs with great potential as novel biomarkers for forensic BFID (Hanson et al 2009;Zubakov et al 2010;Courts and Madea 2011;Wang et al 2013;Sauer et al 2016;Seashols-Williams et al 2016;Sirker et al 2017;Mayes et al 2018;O'Leary and Glynn 2018;Tian et al 2018). In the small number of studies published in this area, however, there is little agreement between them, with only some miRNAs suggested as potential biomarkers for specific fluids overlapping between studies (see Table 1).…”
Section: Body Fluid Identificationmentioning
confidence: 99%
“…Previous published studies reported promising results identifying differentially expressed miRNAs with great potential as novel biomarkers for forensic BFID (Hanson et al 2009;Zubakov et al 2010;Courts and Madea 2011;Wang et al 2013;Sauer et al 2016;Seashols-Williams et al 2016;Sirker et al 2017;Mayes et al 2018;O'Leary and Glynn 2018;Tian et al 2018). In the small number of studies published in this area, however, there is little agreement between them, with only some miRNAs suggested as potential biomarkers for specific fluids overlapping between studies (see Table 1).…”
Section: Body Fluid Identificationmentioning
confidence: 99%
“…Other biomarkers, such as RNAs, have also been proposed and employed in forensic science [29][30][31] and, in addition, with advances in molecular biological techniques, novel approaches based on miRNA profi ling have been developed for a possible forensic application [32]. For example, the circulating miRNAs have been considered as potential tool for identifi cation of sex [33], body fl uids [34,35] or organ tissue types [36].…”
Section: Discussionmentioning
confidence: 99%
“…As most compounds present in blood can also be found in saliva, saliva is suggested to mirror the physiological state of the body [ 18 ]. In this regard, the use of saliva miRs has been extended to exercise evaluation [ 11 ] and forensic body fluid identification [ 19 ].…”
Section: Introductionmentioning
confidence: 99%